Urinary incontinence in climacteric afrodescendant women from the Colombian Caribbean (2019)
INTRODUCTION Urinary incontinence (UI) is a serious health problem in women.1 The International Urogynecological Association and the International Continence Society define UI as the discomfort produced by any involuntary loss of urine through the urethra.2,3 This condition is often under diagnosed because of health professionals seldom ask women about UI, and In turn, women do not discuss the complaint because of embarrassment or the perception that UI is a normal symptom of aging.1 Data from the Study of Women’s Health Across the Nation (SWAN) suggests that belonging to an Afro-American ethnic group and the increase of age were conditions associated with a forty-eight and nine percent respectively, less probability of reporting UI.4 The same authors pointed out that women with greater severity of UI had a high probability of reporting this condition if the symptoms were daily, weekly or monthly, ABSTRACT Background: To assess the prevalence of urinary incontinence (UI) and to identify related factors in Afro-descendant Colombian women. Methods: A cross-sectional study was carried out involving 40-59 year old women from the Colombian Caribbean. Socio-demographic characteristics were recorded and the International Consultation on Incontinence Questionnaire Short-Form (ICIQ-SF) and the 10-item cervantes scale were applied to identify UI and genitourinary symptoms, respectively. Results: A cross-sectional study was carried out involving 40-59-year-old women from the Colombian Caribbean. Socio-demographic characteristics were recorded and the International Consultation on Incontinence Questionnaire Short-Form (ICIQ-SF) and the 10-item cervantes scale were applied to identify UI and genitourinary symptoms, respectively. Conclusions: The prevalence of UI among climacteric afro-descendant women was close to 4%. A history of PIH and PD consumption were related factors.